Characteristics of phase delay in capacitive pick‐off circuits for MEMS resonators. Issue 8 (1st April 2019) - Wu, Haibin; Pang, Qiongxia; Zheng, Xudong; Ma, Zhipeng; Lin, Yiyu; Jin, Zhonghe
Abstract : In this Letter, the authors theoretically and experimentally investigate the characteristics of phase delay in capacitive pick‐off circuits for micro‐electromechanical systems (MEMS) resonators for the first time in history. An analytical model considering the phase delay for capacitive pick‐off circuits is built up in theory. Only when they use their proposed novel modified double side‐band demodulation configuration for resonators to extract motional amplitude and phase, the phase delay of pick‐off circuits can be eliminated and extracted meanwhile in real time. Experiments show that the changing feature of phase delay primarily depends on temperature rather than drive frequency. Experimental results agree well with the theoretical model and reveal the relatively high correlation between the phase delay and temperature. This work provides a new indicator of temperature for resonators, using this phase delay of the pick‐off interface, to make temperature compensation.